Uncovering dynamic evolution in the plastid genome of seven Ligusticum species provides insights into species discrimination and phylogenetic implications - Can Yuan (Nature Portfolio, 2021)
Abstract Ligusticum L., one of the largest members in Apiaceae, encompasses medicinally important plants, the taxonomic statuses of which have been proved to be difficult to resolve. In the current study, the complete chloroplast genomes of seven crucial plants of the best-known herbs in Ligusticum were presented. The seven genomes ranged from 148,275 to 148,564 bp in length with a highly conserved gene content, gene order and genomic arrangement. A shared dramatic decrease in genome size resulted from a lineage-specific inverted repeat (IR) contraction, which could potentially be a promising diagnostic character for taxonomic investigation of Ligusticum, was discovered, without affecting the synonymous rate. Although a higher variability was uncovered in hotspot divergence regions that were unevenly distributed across the chloroplast genome, a concatenated strategy for rapid species identification was proposed because separate fragments inadequately provided variation for fine resolution. Phylogenetic inference using plastid genome-scale data produced a concordant topology receiving a robust support value, which revealed that L. chuanxiong had a closer relationship with L. jeholense than L. sinense, and L. sinense cv. Fuxiong had a closer relationship to L. sinense than L. chuanxiong, for the first time. Our results not only furnish concrete evidence for clarifying Ligusticum taxonomy but also provide a solid foundation for further pharmaphylogenetic investigation.